Doping effect of copper ion (Cu2+) on the conductivity behaviour of ceria (Ce1−xCuxO1−δ) electrolyte. Issue 55 (20th May 2016) - Kumar, Kuldeep; Singh, Nitish Kumar; Park, Hong-Seok; Parkash, Om
Abstract : The doping effect of Cu 2+ in a ceria matrix has been studied using a microwave assisted synthesis technique. Abstract : The doping effect of Cu 2+ in a ceria matrix has been studied using a microwave assisted synthesis technique. Differential thermal and thermogravimetric analyses (DTA–TG) have been performed to understand the thermal response of Cu 2+ doped ceria compositions. Structural and bonding changes in the doped ceria have been analyzed using XRD and FT-IR techniques, respectively. Impedance spectroscopy was performed on silver (Ag) coated pellets, sintered at 1100 °C for 2 hours. The obtained spectra in the temperature range of 300–500 °C and frequency region 1 Hz–1 MHz have been studied, and conductivity behavior has been discussed.